Diagnostic imaging of a rare case of incidental adrenal ganglioneuroma - Muscatella, Gianmichele; Sciacqua, Alessio; Eusebi, Laura; Mannatrizio, Domenico; Mazzucchelli, Roberta; Guglielmi, Giuseppe (Acta Biomedica Atenei Parmensis, 2023)
A 53-year-old man complaining of pain in the right hypochondrium underwent an abdominal ultrasound that showed a left adrenal lesion. Further instrumental investigations (CT and MRI, both with contrast medium) were performed which diagnosed an adrenal ganglioneuroma, confirmed by the histological examination. The patient also underwent an endocrinological examination. The treatment was surgical and consisted of an adrenalectomy through video-laparoscopic access. Adrenal ganglioneuromas are rare tumors but well described and known in the literature. For this reason, this case report has primarily an educational purpose: the totality of the data collected (clinical, laboratoristic, instrumental, and histopathological) constituted a multidisciplinary case, with the focus on imaging.